Knowledge, attitudes and practices of academic and admission staff on the inclusion of students with physical disabilities in the School of Health Care Sciences at Sefako Makgatho Health Sciences University : An exploratory, qualitative descriptive study. - Mphohoni, Mashudu Ronald (Stellenbosch : Stellenbosch University, 2020)
Thesis (MHumanRehabSt)--Stellenbosch University, 2020.